Cell Membrane Deformation Induced by a Fibronectin-Coated Polystyrene Microbead in a 200-MHz Acoustic Trap - Hwang, Jae Youn (2014)
The measurement of cell mechanics is crucial for a better understanding of cellular responses during the progression of certain diseases and for the identification of the cell’s nature. Many techniques using optical tweezers, atomic force microscopy, and micro-pipettes have been developed to probe and manipulate cells in the spatial domain. In particular, we recently proposed a two-dimensional acoustic trapping method as an alternative technique for small particle manipulation. Although the proposed method may have advantages over optical tweezers, its applications to cellular mechanics have not yet been vigorously investigated. This study represents an initial attempt to use acoustic tweezers as a tool in the field of cellular mechanics in which cancer cell membrane deformability is studied. A press-focused 193-MHz single-element lithium niobate (LiNbO(3)) transducer was designed and fabricated to trap a 5-µm polystyrene microbead near the ultrasound beam focus. The microbeads were coated with fibronectin, and trapped before being attached to the surface of a human breast cancer cell (MCF-7). The cell membrane was then stretched by remotely pulling a cell-attached microbead with the acoustic trap. The maximum cell membrane stretched lengths were measured to be 0.15, 0.54, and 1.41 µm at input voltages to the transducer of 6.3, 9.5, and 12.6 V(pp), respectively. The stretched length was found to increase nonlinearly as a function of the voltage input. No significant cytotoxicity was observed to result from the bead or the trapping force on the cell during or after the deformation procedure. Hence, the results convincingly demonstrated the possible application of the acoustic trapping technique as a tool for cell manipulation.